Implikasi Penerapan Work From Home terhadap Beban Kerja Fisik Pekerja dalam Perspektif Ergonomi - Edit Rusnita; Adam Setiawan (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Work From Home (WFH) is a new model that is currently beginning to replace the conventional work model. The adoption of WFH has increased significantly since the COVID-19 pandemic and continouos to be implemented by various organizations today because it is seen as a way to increase work flexibility, reduce operational costs, and promote a better work-life-balance. Although it offers flexibility and efficiency, the impelementation of WFH has the potential to increase physical workload resulting from less-than-ergonomic working conditions. This study aims to analyze the implications of WFH on workers’ physical workload from an ergonomic perspective. The method used was literature review with a systematic review based on the SPIDER model (Sample, Phenomenon of Interest, Design, Evaluation, and Research Type). The results show that WFH increases the risk of musculoskeletal disorders, particulary neck pain and lower back pain due to static work posture. The application of ergonomic principles, employee education, and the provision of adequate work facilities are necessary to reduce physical workload and support employee health and productivity while working from home.